Transport of angiotensin converting enzyme and renin dual inhibitory peptides LY, RALP and TF across Caco-2 cell monolayers. (August 2017) - Yang, Yi-Jie; He, Hai-Yan; Wang, Feng-Zhang; Ju, Xing-Rong; Yuan, Jian; Wang, Li-Feng; Aluko, Rotimi E.; He, Rong
Highlights: The stability of the ACE- and renin-inhibitory peptides was investigated. The inhibition activity was estimated by non-linear regression analysis. LY had the potential to be transported intact into blood circulation. The fragments of RALP after transport had potential ACE- and renin- activity. Abstract: In order for peptides to exert physiological effects, intact transportation or absorption of their degradation fragments with bioactive potency is required. In this study, Caco-2 cell model was employed to investigate the stability of ACE- and renin-inhibitory peptides LY, RALP and TF during cellular absorption. Apparent permeability coefficient was 3.49, 0.32, and 0.94 × 10 −6  cm/s for LY, RALP and TF, respectively. LY had the highest infiltration yield of 6.59%, compared to RALP (0.51%) and TF (2.44%) at 180 min. Peptides collected from the basolateral sides after 180 min had ACE-inhibitory levels of 33.03%, 14.22% and 14.33% with different initial concentrations for LY (2 mM), RALP (1 mM) and TF (3 mM), respectively. In contrast, renin-inhibitory activities were lower at 9.52% (LY) and 7.37% (RALP) while TF had no inhibition. Thus, dipeptides could be more easily absorbed for controlling hypertension and the fragments of RALP had potential antihypertensive properties.